2011
DOI: 10.1016/j.intell.2011.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Beyond IQ: A latent state-trait analysis of general intelligence, dynamic decision making, and implicit learning

Abstract: The present study investigated cognitive performance measures beyond IQ. In particular, we investigated the psychometric properties of dynamic decision making variables and implicit learning variables and their relation with general intelligence and professional success. N =173 employees from different companies and occupational groups completed two standard intelligence tests, two dynamic decision making tasks, and two implicit learning tasks at two measurement occasions each. We used structural equation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 28 publications
7
88
1
3
Order By: Relevance
“…For the purposes of our analyses, we defined LST parameters ≤.30 as small, between .30 and .60 as moderate, and ≥.60 as great, as consistencies of well-known intelligence and personality tests all exceeded this threshold value [51,52]. Note that these cut-offs should only be treated as heuristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purposes of our analyses, we defined LST parameters ≤.30 as small, between .30 and .60 as moderate, and ≥.60 as great, as consistencies of well-known intelligence and personality tests all exceeded this threshold value [51,52]. Note that these cut-offs should only be treated as heuristics.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we used previous applications of LST theory in individual differences research on mental abilities and personality traits as benchmarks. Danner et al [51] calculated the LST parameters of intelligence tests and reported consistencies ranging from .67 to .72 and reliabilities ranging from .86 to .83, which they evaluated as "great". In comparison, method-specificities of intelligence tests ranged from .13 to .24 and were evaluated as "small".…”
Section: Discussionmentioning
confidence: 99%
“…Gebauer and Mackintosh, 2007;Kaufman et al, 2009). Danner et al (2011) find that cognitive ability simultaneously predicts professional success and success at learning an artificial grammar. A link between cognitive ability and learning also exists in educational settings: in particular, cognitive ability helps to predict schooling attainment (e.g., Neisser et al, 1996;Heckman et al, 2006;Cunha et al, 2010;Burks et al, 2014;.…”
mentioning
confidence: 89%
“…Correlations between incidental learning and IQ have been small -but not usually zero, and in at least one or two studies have indeed been significant: for example, Danner et al (2011) reported a significant correlation of .32 between artificial grammar learning and measures of fluid intelligence in a sample of 173 adultsalthough this compared with a correlation of .86 between the same IQ measures and a problem solving task. Salthouse et al (1999) also found a significant correlation between serial reaction time and IQ.…”
Section: Figure 4 About Here Pleasementioning
confidence: 99%